MATHEMATIC METHODS IN STUDYING INTEREST RISK OF LONG-TERM BONDS - Natalia V. Popova (Вестник Российского экономического университета имени Г. В. Плеханова, 2017)
The article investigates the influence of one parameter of bond, i. e. due date on its interest risk. This problem for long-term bonds has not been fully studied in theory. Two ways of solving the problem of affecting the bond interest risk by the due date were compared. To do this the results were used that had been obtained by the author through solving tasks about the dependence of Macaulay duration on the due date and relative changes in the bond price. In both cases the task was solved in conditions of certainty with horizontal nature of time structure of interest rates and parallel shifting. For these tasks theorems of digital rows and differentiated functions were applied. The comparison of two ways of solving the task shows similarity of results, which makes it possible to specify the dependence of the interest risk on the due date for long-term bonds.